Towards in vivo dosimetry for contrast enhanced synchrotron stereotactic radiation therapy based on iodine x-ray spectroscopy - Richard Hugtenburg (Biomedical Physics & Engineering Express, 2018)
The first trial applications of Contrast-Enhanced Synchrotron Stereotactic Radiation Therapy (SSRT) is underway since June 2012 at the European Synchrotron Radiation Facility (ESRF) in Grenoble (France). The phase I-II clinical trial is designed to test the feasibility and safety of SSRT through a dose escalation protocol. Contrast enhanced radiotherapy achieves localized dose enhancement due to higher photoelectric effect rate in the target. This increase is obtained through the preferential uptake of high-Z media (iodine) in the tumoral area combined with irradiations with medium energy synchrotron x-rays. In vivo dosimetry (i.e. experimental dosimetry in real time during the treatment) would be a serious added value to the project, in terms of online dose monitoring and quality control. It is challenging to perform in vivo dosimetry with the currently available conventional clinical techniques. In this work we investigated a method using x-ray fluorescence detection to derive the iodine concentration contained in a tumor during the treatment of a patient, as a first step towards in vivo dosimetry. A mean iodine concentration of 0.33 ± 0.22 mg/ml has been retrieved in the tumor of the patient compared to 2 mg/ml expected would correspond to 3% local dose enhancement in the tumor. Further work will be performed to improve the attenuation correction method. The expected amount of iodine should be 2 mg/ml in the tumor (20% dose enhancement). This method is suitable to detect iodine in the target but has some problem in quantifying the real amount of iodine present during the irradiation.